A Discussion on the Position of Weaving in the Society of Prehistoric Britain - Helen Poulter (EXARC, 2021)
There have been several recent experiments on using warp-weighted looms in Demark, Italy and Greece, some in Roman houses (Andersson Strand, 2015; Dimova, 2016). The experiments, in particular those in Denmark and Netherlands, took place in the typical rectangular longhouses used in their respective prehistories, unlike 'Britain's predominant roundhouses. There have been little, if any, experiments in using a warp-weighted loom in a roundhouse. Specifically, we set out to examine the internal environment and its effects on the loom, including its impact on the house. It has been suggested that textile production in prehistoric Britain was done by women, as part of the home's duties. This is now starting to be questioned as there is little evidence one way or the other. However, due to past archaeologists accepting gender-specific roles, this is still promoted in many museums displays. Yet, the history of weaving and textile production in Britain has been dominated by both sexes at different times. There is more evidence in the Roman, Saxon and Viking periods, due to written sources. However, is this a true reflection of the time or our perceptions and social acceptance?